2021
DOI: 10.1038/s41598-021-85128-2
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive prenatal testing for β-thalassemia by targeted nanopore sequencing combined with relative haplotype dosage (RHDO): a feasibility study

Abstract: Noninvasive prenatal testing (NIPT) for single gene disorders remains challenging. One approach that allows for accurate detection of the slight increase of the maternally inherited allele is the relative haplotype dosage (RHDO) analysis, which requires the construction of parental haplotypes. Recently, the nanopore sequencing technologies have become available and may be an ideal tool for direct construction of haplotypes. Here, we explored the feasibility of combining nanopore sequencing with the RHDO analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Recent advances in single molecule long-read sequencing platforms, such as those developed by Oxford Nanopore Technologies (ONT, Oxford, U.K.) [ 61 ] and Pacific Biosciences (PacBio, Menlo Park, CA, U.S.A.) [ 62 ], also have the potential to enable proband-free RHDO, as demonstrated in a recent study with relevance to β-thalassaemia, whereby ONT long-read sequencing was used to increase the length of individual haplotype blocks used for phasing analysis, and consequently improve statistical robustness [ 63 ]. In this study, Jiang and colleagues reported a failure to determine the maternal haplotype in one family as the closest heterozygous SNP was located outside of the PCR fragment boundary and thus not linkable to the variant-of-interest [ 63 ]. Further investigation is required to determine how common such local regions of homozygosity may be, and how this could negatively impact the utility of maternal haplotype phasing by long-read sequencing.…”
Section: In the Developmental Pipelinementioning
confidence: 99%
“…Recent advances in single molecule long-read sequencing platforms, such as those developed by Oxford Nanopore Technologies (ONT, Oxford, U.K.) [ 61 ] and Pacific Biosciences (PacBio, Menlo Park, CA, U.S.A.) [ 62 ], also have the potential to enable proband-free RHDO, as demonstrated in a recent study with relevance to β-thalassaemia, whereby ONT long-read sequencing was used to increase the length of individual haplotype blocks used for phasing analysis, and consequently improve statistical robustness [ 63 ]. In this study, Jiang and colleagues reported a failure to determine the maternal haplotype in one family as the closest heterozygous SNP was located outside of the PCR fragment boundary and thus not linkable to the variant-of-interest [ 63 ]. Further investigation is required to determine how common such local regions of homozygosity may be, and how this could negatively impact the utility of maternal haplotype phasing by long-read sequencing.…”
Section: In the Developmental Pipelinementioning
confidence: 99%
“…Preimplantation testing during in vitro fertilization and the application of preimplantation gene testing via the detection of pathogenic structural variants in embryos could be of key importance [ 15 ]. For targeted prenatal testing, ONT has been successfully applied for the testing of fetal DNA from maternal blood samples [ 16 ]. As for postnatal testing, for whole-genome sequencing and diagnosis, a world-record time of 7 h and 18 min has been achieved by the ONT approach [ 17 ].…”
Section: Molecular Testing—timing and Approachmentioning
confidence: 99%
“…(2) Targeted molecular testing in a time-dependent manner for the establishment of an actionable diagnosis, e.g., gene therapy, a modified therapeutical approach and enzyme replacement therapy. Recently, a feasibility study designed to address targeted gene analysis from noninvasive prenatal testing (NIPT) samples using ONT has been described [ 16 ]. ONT provides a direct construction of haplotypes, through relative haplotype dosage analysis from maternal blood plasma, which is of importance in diseases such as ß-thalassaemia, spinal muscular atrophy, Duchenne’s and Becker’s muscular dystrophies and Hunter’s disease [ 16 ].…”
Section: Where To Fit Long-read Sequencing In Clinical Genomics?mentioning
confidence: 99%
“…This fetal DNA source can be obtained through venipuncture, which is safer than previously described amniocentesis and chorionic villi sampling. Moreover, NGS-based approaches combined with conventional relative haplotype dosage (RHDO) analysis is a technique which is increasingly adapted into the NIPD protocol due to its feasibility and low-cost ( 43 ). NGS provides efficient means of constructing parental haplotypes to assess fetal genotypes, i.e., by removing the needs of complicated haplotypic block/proband analysis ( 44 ).…”
Section: Introductionmentioning
confidence: 99%